Ethical heritage interpretation in Indigenouscontexts: An ethnographic case study / Christy Bidder - Bidder, Christy (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus Page Range, 2020)
This paper is an ethnographic case study conducted to examine the ethics of heritage interpretation within Indigenous contexts. The Mari-Mari Cultural Village located in Sabah, which is Malaysian Borneo as the study area. The main objective is to investigate the ethical culture of self-criticality, and the reflection was present or absent in the interpretation conducted by the on-site guides at the cultural village. It also aimed to uncover other potential ethical issues that might impede the appropriate interpretation of the Indigenous cultures depicted at the cultural village. Personal interviews were conducted with selected on-site guides, and direct observations were made through participation in the guided tours. Interviewed responses were transcribed and analyzed using an iterative thematic coding approach to identify major themes or main ideas. The results indicated two principal ethical issues affecting the heritage interpretation conducted by on-site guides of MMCV. Thefirstissuewaslackself- criticality and reflection culture, which the on-site guides were deficient in the quality of interrogating themselves and their sources of research and sourcing. The second issue was associated with the notion of ethnic intruders where the same on-site guide would interpret not just the culture related to his/her own Indigenous background, but also their cultures whom he/she had little knowledge about it. The research concluded with an emphasis to ensure interpretation of Indigenous cultures were made in a proper manner that would significantly improve but at the same time not to erase or distort the understandings of the Indigenous cultures.